Optimalization of the Form of a Building with an Arbitraty Base - Adamski, M. (Engineering Transactions, 1994)
The present paper is devoted to the formulation and solution of the problem of multicriterial optimization of the form of an energy-saving building with vertical walls and constant volume and height. The base of the building is described by two arbitrary curves. The criterion of minimum building cost and minimum annual heating cost are assumed for optimization. The decision variables of the problem are the curves describing the base of the building. An algorithm for the EUREKA software package has been elaborated. The considerations are illustrated by a numerical example.